2017
DOI: 10.1016/j.concog.2016.07.003
|View full text |Cite
|
Sign up to set email alerts
|

The hubris hypothesis: The downside of comparative optimism displays

Abstract: According to the hubris hypothesis, observers respond more unfavorably to individuals who express their positive self-views comparatively than to those who express their positive self-views non-comparatively, because observers infer that the former hold a more disparaging view of others and particularly of observers. Two experiments extended the hubris hypothesis in the domain of optimism. Observers attributed less warmth (but not less competence) to, and showed less interest in affiliating with, an individual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(31 citation statements)
references
References 41 publications
2
25
0
4
Order By: Relevance
“…More specifically, observers are hypothesized to relatively dislike explicit braggarts because they infer that these braggarts hold a negative view of others and hence of them. In previous studies, mediation analyses confirmed this reasoning (Hoorens et al, 2017; Van Damme, Hoorens, & Sedikides, 2016).…”
Section: The Hubris Hypothesis: Why Self-superiority Claims May Entaisupporting
confidence: 56%
See 2 more Smart Citations
“…More specifically, observers are hypothesized to relatively dislike explicit braggarts because they infer that these braggarts hold a negative view of others and hence of them. In previous studies, mediation analyses confirmed this reasoning (Hoorens et al, 2017; Van Damme, Hoorens, & Sedikides, 2016).…”
Section: The Hubris Hypothesis: Why Self-superiority Claims May Entaisupporting
confidence: 56%
“…Participants responded to affiliation questions adapted from Helweg-Larsen, Sadeghian, and Webb (2002; Hoorens et al, 2017). Two of these here served as an unobtrusive measure of liking, namely, if the braggart was pleasant to be around (1 = not at all , 7 = definitely pleasant ) and if participants would like to have the braggart as a friend (1 = not at all , 7 = very much ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This might be so because informants infer that the self-enhancing person holds a disparaging view of others, including a disparaging view of the informant herself or himself. Informants might then evaluate the person unfavorably, as they are personally offended by such inferred direct and self-serving social comparisons (Hoorens, Pandelaere, Oldersma, & Sedikides, 2012; Hoorens, Van Damme, Helweg-Larsen, & Sedikides, 2017; Van Damme, Hoorens, & Sedikides, 2016).…”
Section: Part Ii: Interpersonal Adjustmentmentioning
confidence: 99%
“…Impression mismanagement occurs when people are oblivious to hubris, namely, the impact that their self‐aggrandizing displays can have on the audience's self‐views. A program of research systematically varied an actor's self‐presentations (using different types of self‐enhancing and non‐self‐enhancing claims) and assessed the inferences that observers make about the actor (e.g., liking) and also the inferences that they make about the actor's opinion of others in general as well as of observers in particular (Hoorens, Pandelaere, Oldersma, & Sedikides, ; Hoorens, Van Damme, Helweg‐Larsen, & Sedikides, ; van Damme, Hoorens, & Sedikides, ).…”
Section: Recent Insights On Impression Mismanagement: the Inept Self‐mentioning
confidence: 99%